Memory for emotional simulations: Remembering a rosy future - Szpunar, Karl K. (2011)
Mental simulations of future experiences are often concerned with emotionally arousing events. Although it is widely believed that mental simulations enhance future behavior, virtually nothing is known about the mnemonic fate of these simulations over time or whether emotional simulations are especially well-remembered. We used a novel paradigm, combining recently developed methods for generating future event simulations and well-established memory testing procedures, to examine the retention of positive, negative, and neutral simulations over multiple delays. We found that with increasing delay, details associated with negative simulations become more difficult to remember than details associated with positive and neutral simulations. We suggest that these delay-by-emotion interactions reflect the mnemonic influence of fading affect bias, where negative reactions fade more quickly than positive ones, resulting in a tendency to remember a rosy simulated future. We also discuss implications for affective disorders such as depression and anxiety.